Genomic sequence and phylogenetic analyses of two novel orthoreovirus strains isolated from Pekin ducks in 2014 in Germany - Farkas, Szilvia L.; Varga-Kugler, Renáta; Marton, Szilvia; Lengyel, György; Palya, Vilmos; Bányai, Krisztián (Virus research, 2018)
•The genome sequence and phylogenetic analysis of two novel orthoreovirus strains are described.•Strain 2533/4/1-10 is probably a triple reassortant.•Strain 2533/6/1-10 might have been acquired from an unknown natural host species. Complete genomic sequences of two orthoreovirus strains, D2533/4/1-10 and D2533/6/1-10, isolated from Pekin ducklings in Germany have been determined. Pairwise sequence comparisons and phylogenetic analyses indicated that strain D2533/4/1-10 might have acquired its genomic segments from three different origins, from classical and novel waterfowl reoviruses, and a yet unknown orthoreovirus strain. D2533/6/1-10 proved to be only distantly related to previously described orthoreoviruses. Reassortment, host species transmission events, and successful adaptation of novel variants may signify a challenge for animal health and maintenance of economic production.